Análise do perfil de imunossenescência em células T de pacientes em diferentes estágios de infecção por SARS-CoV-2 - Sarmento, Isabela Valim (2022)
COVID-19 is a disease caused by SARS-CoV-2 that affects the respiratory system, causing lung damage that can progress to severe acute respiratory syndrome (ARDS), acute increase in inflammatory cytokines (cytokine storm), hepatic, cardiovascular, and renal damage. An exacerbated inflammatory environment, as seen in COVID-19, can lead to changes in the profile of differentiation and functionality of T cells. These factors promote the expansion of senescent T cells, which is defined by the progressive loss of costimulatory receptors (CD27 and CD28), DNA damage, p38 MAPK activation, and loss of proliferative capacity. The accumulation of senescent T cells has been associated with the immunopathogenesis of many diseases. However, it is still poorly understood in the context of COVID-19. This work evaluated the clinical/laboratory profile of patients with COVID-19, clinically classified between oligosymptomatic, moderate, and severe. In addition, we evaluated senescent phenotype characteristics in T cell compartments. Our results demonstrate alterations in several laboratory parameters such as leukocytosis, neutrophilia, eosinopenia, monocytosis, lymphopenia, increased LDH, direct bilirubin, triglycerides, C-reactive protein, urea, and creatinine. In addition, patients with COVID-19, especially the severe and moderate groups, showed changes in blood gas with disturbances in arterial pH and PCO2. Our phenotypic analyses showed a decrease in cell viability in the groups most affected by the disease (moderate and severe), with changes in the frequencies of CD4+ and CD8+ T cells, increased DNA damage identified by γH2Ax phosphorylation, as well as increased expression of MAPK p38 that is linked to senescence. Furthermore, compared to the oligosymptomatic group, critically ill patients showed an accumulation of highly differentiated populations, identified by the CD28-CD27- and terminal memory cells (T EMRA) subgroups. Thus, patients with the most severe shape of COVID-19 exhibit a senescent T-cell phenotype, which may be one of the aggravating factors for this disease.